Voices of Proficiency: Insights into EFL Pronunciation Teaching Challenges in Indonesian Middle School Teachers - Fitriana, Dina; Agustian, Agung Farid (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2025)
This study investigates English pronunciation teaching practices, challenges, and effectiveness in Indonesian senior middle schools. It aims to identify specific barriers teachers face and develop recommendations for improving pronunciation instruction. The research focuses on internal factors, such as teachers' self-proficiency and instructional techniques, and external factors, including curriculum constraints and student motivation. Interviews with four English teachers revealed that reading aloud is a common strategy for teaching pronunciation, with Teacher 1 using report texts and Teacher 2 incorporating role play. Teachers 1 and 2 actively participate in the MGMP discussion forum to enhance their teaching methods, whereas Teachers 3 and 4 value their phonetics training from college. The study identifies critical challenges, such as students' lack of practice, native language interference, and motivational issues. Teachers 1 and 2 noted that students' pronunciation struggles are compounded by their reliance on their mother tongue and limited practice. Recommendations include integrating dedicated pronunciation practice into the curriculum and using interactive activities to enhance students' engagement and proficiency in English pronunciation.